Pemanfaatan Media Sosial Dalam Pembelajaran di SDIT At-Taqwa Surabaya - Nadia Risya Faridah; Nasihkol Haromain (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The development of increasingly sophisticated technology makes the world of education evolve to be more flexible. Social media was chosen as one of the efforts of educational institutions to carry out online learning during the Covid-19 pandemic. This research aims to determine the use of social media in learning at the elementary school level, the potential of social media in learning and the advantages and disadvantages of social media in learning. The results of the research show that social media in learning are Zoom Meeting, WhatsApp, YouTube and Instagram which have the potential to increase students' interest and motivation to more respect about assignments. In its implementation, there are advantages and disadvantages to social media when used in learning, therefore the assistance of teachers and parents is very necessary.